Biopore Infiltration Techniques and Vegetative Maintenance for Sustainable Water Resource Management - Joko Wibowo; Hosniyeh Hosniyeh (Salwatuna : Jurnal Pengabdian Masyarakat, 2025)
A major problem faced by the people of Sekarbanyu village was the water scarcity, Sumbermanjing Wetan district, Malang regency, especially during the dry season. Changes in land use and the lack of public awareness of the conservation of natural resources escalated this situation. This community service program aimed to define and investigate the implementation of a water source sustainability initiative program through the utilization of biopore techniques and the management of water-absorbing plants, applying a Participatory Action Research (PAR) framework according to Maqoshid al-Syari’ah principles. The methods applied in the community service program included observation, interviews, group discussions, and collaborative action with the community and village government. The results showed that biopores and reforestation facilitated the improvement of soil absorption, reduced water scarcity, and increased community awareness and participation in environmental preservation. The program also facilitated a synergy between technical solutions and Islamic spiritual values, making it a potential prototype to be replicated, adopted, and adapted in other regions with similar conditions.